The Mediating Role of Environmental Performance on the Relationship between Corporate Governance Mechanisms and Environmental Disclosure - Razieh Adinehzadeh,; Romlah Jaffar,; Zaleha Abdul Shukor,; Mara Ridhuan Che Abdul Rahman, (Asian Academy of Management Journal of Accounting and Finance, 2018)
Despite the growing number of environmental rules and regulations, there are relatively few studies that consider the whole association between environmental performance, corporate governance and environmental reporting. Therefore, the objectives of the study are to investigate the association between corporate governance and environmental disclosures quality and the mediating role of environmental performance in this relationship. Sample of study consists of 344 companies listed on Bursa Malaysia for the year of 2013. Environmental performance (EP) data were collected from the Malaysia Department of the Environment (DOE). Corporate Governance (CG) data were collected from the annual report of sample companies using corporate governance index based on Malaysian Code on Corporate Governance (MCCG). The results of study show that corporate governance is positively associated with environmental performance and its disclosure. The results also show that environmental performance partially mediates the relationship between corporate governance and environmental disclosure quality. This study serves as a valuable input to top management regarding the importance of corporate governance mechanisms towards the establishment of environmental related policies and strategies that help to improve environmental performance. The findings also provide an impetus for companies to develop specific abilities and resources in prioritised areas that are of a concern to relevant stakeholders.